Cauchy Problem for a Generalized Nonlinear Dispersive Equation (Journal of Partial Differential Equations, 2020)
The solvability of global smooth solution for the Cauchy problem of a generalized nonlinear dispersive equation is studied by using the continuation method. In addition, the convergences of solution for this problem are also discussed.